Hope as a predictor of internalizing behavior problems among adolescents in Yogyakarta, Indonesia - Izzaty, Rita Eka; Ayriza, Yulia; Mutia, Cania; Istikomah, Fatonah (Universitas Mercu Buana Yogyakarta, 2023)
The prevalence of internalizing behavior problems, namely depression, anxiety, and stress, among adolescents has increased globally. Poor levels of hope have been previously identified in a vast body of literature as one of the factors which has contributed to a large number of internalization behaviour problems . This study aimed to examine hope as a significant predictor of depression tendencies, anxiety, and stress among adolescents in Yogyakarta, Indonesia using an incidental sampling method. The Depression Anxiety Stress Scales-21 (DAAS-21) and the Snyder's Hope Scale were modified and validated for an online survey. Four hundred Indonesian teenagers between 12 and 21 years took part in the online poll. The data were analyzed using regression analysis to evaluate the correlations between internalizing behavioral issues and hope. Based on the regression analysis, this study found that hope had a negative correlation with stress (r = -0.16, p .01; BCa 95% CI [-0.28; 0.05]), anxiety (r = -0.20, p .01; BCa 95% CI [-0.31; 0.10), and depression (r = -0.36, p .01; BCa 95% CI [-0.45; -0.26). Furthermore, it was found that hope could predict lower levels of stress, anxiety, and depression in the sample (t = -3.27; B = -.13; p .01; BCa 95% CI [-.29; -.05]).